Strategic cyber security management - Trim, Peter R. J.; Lee, Yang-Im (New York, NY : Routledge, 2023)
"This textbook places cyber security management within an organizational and strategic framework, enabling students to develop their knowledge and skills for a future career. The reader will learn to: evaluate different types of cyber risk, carry out a threat analysis and place cyber threats in order of severity, formulate appropriate cyber security management policy, establish an organization-specific intelligence framework and security culture, devise and implement a cyber security awareness programme, and integrate cyber security within an organization's operating system. Learning objectives, chapter summaries and further reading in each chapter provide structure and routes to further in-depth research. Firm theoretical grounding is coupled with short problem-based case studies reflecting a range of organizations and perspectives, illustrating how the theory translates to practice, with each case study followed by a set of questions to encourage understanding and analysis. Non-technical and comprehensive, this textbook shows final year undergraduate students and postgraduate students of Cyber Security Management, as well as reflective practitioners, how to adopt a pro-active approach to the management of cyber security. Online resources include PowerPoint slides, an instructor's manual, and a test bank of questions"--
Includes bibliographical references and index.
Keywords: Business enterprises -- Computer networks -- Security measures; Computer security; Computer crimes -- Prevention; Corporations -- Security measures